Assessing the Impact of Planned Social Change* - Campbell, Donald T. (Journal of MultiDisciplinary Evaluation, 2011)
Originally published as Paper #8, Occasional Paper Series, December, 1976* Reprinted with permission of The Public Affairs Center, Dartmouth College. Preparation of this paper has been supported in part by grants from the Russell Sage Foundation and the National Science Foundation, Grant Number SOC-7103704-03. A version of this paper was presented to the Visegrad, Hungary, Conference on Social Psychology, May 5-10, 1974.